Evaluation of cumulative cognitive deficits from electroconvulsive therapy. (March 2016) - Kirov, George G.; Owen, Laura; Ballard, Hazel; Leighton, Adele; Hannigan, Kara; Llewellyn, Danielle; Escott-Price, Valentina; Atkins, Maria
Abstract : Background: Electroconvulsive therapy (ECT) is the most effective acute treatment for severe depression, but widely held concerns about memory problems may limit its use. Aims: To find out whether repeated or maintenance courses of ECT cause cumulative cognitive deterioration. Method: Analysis of the results of 10 years of cognitive performance data collection from patients who have received ECT. The 199 patients had a total of 498 assessments, undertaken after a mean of 15.3 ECT sessions (range 0–186). A linear mixed-effect regression model was used, testing whether an increasing number of ECT sessions leads to deterioration in performance. Results: The total number of previous ECT sessions had no effect on cognitive performance. The major factors affecting performance were age, followed by the severity of depression at the time of testing and the number of days since the last ECT session. Conclusions: Repeated courses of ECT do not lead to cumulative cognitive deficits. This message is reassuring for patients, carers and prescribers who are concerned about memory problems and confusion during ECT.